2018
DOI: 10.3892/etm.2018.6039
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑30b protects myocardial cell function in patients with acute myocardial ischemia by targeting plasminogen activator inhibitor‑1

Abstract: The aim of the present study was to determine the expression of plasminogen activator inhibitor-1 (PAI-1) and microRNA (miR)-30b in the blood of patients with acute myocardial ischemia (AMI) and in the blood and myocardial tissue of mice with AMI. In addition, the present study aimed to identify the mechanism of action of miR-30b in AMI. A total of 36 patients with AMI were included in the present study and 28 healthy subjects were included as a control. Peripheral blood was collected from all subjects. For an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The leading cause of morbidity in the Western world is acute myocardial ischemia (AMI), which is caused by an imbalance between the blood supply to the heart and the demand of the myocardium [1, 2]. The primary features of AMI are hypoxia, cell ischemia and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The leading cause of morbidity in the Western world is acute myocardial ischemia (AMI), which is caused by an imbalance between the blood supply to the heart and the demand of the myocardium [1, 2]. The primary features of AMI are hypoxia, cell ischemia and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Haque et al [ 50 ] described that increased miR-30b inhibits endogenous catalase expression in human cells. In addition, in acute myocardial ischaemic patients a reduction in miR-30b levels in serum has been described [ 51 ]. LncRNAs are key molecules in telomere integrity, highlighting the role of TERRA and GUARDIN .…”
Section: Discussionmentioning
confidence: 99%
“…miR-30b expression was decreased in the peripheral blood of patients with acute myocardial ischemia (AMI) and in the peripheral blood and myocardial tissue in an AMI murine model ( 99 ). Based on the murine model, it was also suggested that miR-30b exerted a myocardial protective effect by targeting PAI-1( 101 ).…”
Section: Role Of Mir-30b In Cardiovascular Diseasementioning
confidence: 99%